Pengaruh Terapi Dingin Ice Massage Terhadap Perubahan Intensitas Nyeri Pada Penderita Low Back Pain - Eva Nurlis; Bayhakki '; Erika ' (Fakultas Keperawatan, Universitas Riau, 2012)
Low back pain was suffered by almost 90% of human beings during their lives, particularly for people who have risk factors oflow back pain. One of the non-pharmacological therapy that can be used to reduce low back pain is cold therapy namely icemassage. The objective of this study was to investigate effect of delivering ice massage to change of pain intensity on people withlow back pain. quasi experimental design one group (pretest-posttest) design was used in this study. Intervention was deliveredto 30 respondents with no control group. Independent t-test was used to analyze the data. Result of this study showed that effectof delivering ice massage on change of pain intensity that was reduce of pain whereas mean of pain intensity before therapy was5,53 to 2,57 after therapy with p value 0,000 (alpha 0,05). Based on the result of this study, ice therapy can be alternativetherapy in order to reduce pain for people with low back pain.Keywords: cold therapy, ice massage, low back pain, pain.